The Relationship Of Prolonged Party In Particular Women And The Incident Of Neonatorum Asphyxia At Rskdia Pertiwi, Makassar City - Siti Maryam; Dwi Ghita; Andi Sulfikar; Indah Restika BN (Ammar Dharma Foundation, 2024)
Background: Prolonged labor is a latent phase lasting more than 8 hours. Labor has been ongoing for 12 hours or more but the baby has not been born. Neonatal asphyxia is the failure to breathe spontaneously and regularly at birth or shortly after birth, characterized by hypoxemia, hypercarbia, and acidosis. Asphyxia during delivery can be caused by oxygen deficiency which can result in Prolonged Labor.Objective: to determine the Relationship of Prolonged Labor in Delivering Mothers with the Incidence of Neonatal Asphyxia at RSKDIA Pertiwi Hospital, Makassar City.Methods: The type of research used in this study is quantitative research with a descriptive research method using a cross-sectional study. Sampling was done using accidental sampling technique. The sample in this study were mothers who gave birth at RSKDIA Pertiwi Hospital, Makassar City. The sample in this study were 32 samples. Data processing was carried out using SPSS chi-square. Data collection used observation sheets with research results statistically tested using descriptive statistics frequency and Chi Square Test. Results: Based on statistical tests, it was found that out of 32 samples (100%) mothers who experienced Prolonged Labor were 21 people (65.6%), while mothers who did not experience Prolonged Labor were 11 people (34.4%). The number of babies born with neonatal asphyxia was 25 babies (78.1%), while babies born without Neonatal Asphyxia were 7 babies (21.9%). Based on the Chi-square test, the significance value obtained was ρ = 0.020 < ɑ 0.05 then Ha was accepted and H0 was rejected, meaning there was a Relationship between Prolonged Labor in delivering mothers with the Incidence of Neonatal Asphyxia at RSKDIA Pertiwi Hospital, Makassar City.Conclusion: Based on the results of the research conducted, theories, and previous research, it can be concluded that there is a Relationship between Prolonged Labor in delivering mothers with the Incidence of Neonatal Asphyxia at RSKDIA Pertiwi Hospital, Makassar City.